Buddhist World of Southeast Asia, The : Second Edition - Swearer, Donald K., 1934- (Book collections on Project MUSE., 2010)
"An unparalleled portrait, Donald K. Swearer's The Buddhist World of Southeast Asia has been a key source for all those interested in the Theravada homelands since the work's publication in 1995. Expanded and updated, the second edition offers this wide-ranging account for readers at the beginning of the twenty-first century." "Swearer shows Theravada Buddhism in Southeast Asia to be a dynamic, complex system of thought and practice embedded in the cultures, societies, and histories of Thailand, Myanmar (Burma), Laos, Cambodia, and Sri Lanka. The work focuses on three distinct yet interrelated aspects of this milieu. The first is the popular tradition of life models personified in myths and legends, rites of passage, festival celebrations, and ritual occasions. The second deals with Buddhism and the state, illustrating how King Asoka serves as the paradigmatic Buddhist monarch, discussing the relationship of cosmology and kingship, and detailing the rise of charismatic Buddhist political leaders in the postcolonial period. The third is the modern transformation of Buddhism: the changing roles of monks and laity, modern reform movements, the role of women, and Buddhism in the West."--Jacket